Solve for x
x=-\frac{62500000000000y}{124614666716641}+20
Solve for y
y=-\frac{124614666716641x}{62500000000000}+39.87669334932512
Graph
Share
Copied to clipboard
y = 2 \cdot 0.996917333733128 {(20 - x)}
Evaluate trigonometric functions in the problem
y=1.993834667466256\left(20-x\right)
Multiply 2 and 0.996917333733128 to get 1.993834667466256.
y=39.87669334932512-1.993834667466256x
Use the distributive property to multiply 1.993834667466256 by 20-x.
39.87669334932512-1.993834667466256x=y
Swap sides so that all variable terms are on the left hand side.
-1.993834667466256x=y-39.87669334932512
Subtract 39.87669334932512 from both sides.
\frac{-1.993834667466256x}{-1.993834667466256}=\frac{y-39.87669334932512}{-1.993834667466256}
Divide both sides of the equation by -1.993834667466256, which is the same as multiplying both sides by the reciprocal of the fraction.
x=\frac{y-39.87669334932512}{-1.993834667466256}
Dividing by -1.993834667466256 undoes the multiplication by -1.993834667466256.
x=-\frac{62500000000000y}{124614666716641}+20
Divide y-39.87669334932512 by -1.993834667466256 by multiplying y-39.87669334932512 by the reciprocal of -1.993834667466256.
y = 2 \cdot 0.996917333733128 {(20 - x)}
Evaluate trigonometric functions in the problem
y=1.993834667466256\left(20-x\right)
Multiply 2 and 0.996917333733128 to get 1.993834667466256.
y=39.87669334932512-1.993834667466256x
Use the distributive property to multiply 1.993834667466256 by 20-x.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}